2005
DOI: 10.1523/jneurosci.1251-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Kv1.3 Channels Contribute to Their Ability to Kill Neurons

Abstract: Many CNS disorders involve an inflammatory response that is orchestrated by cells of the innate immune system: macrophages, neutrophils, and microglia (the endogenous CNS immune cell). Hence, there is considerable interest in anti-inflammatory strategies that target these cells. Microglia express Kv1.3 (KCNA3) channels, which we showed previously are important for their proliferation and the NADPH-mediated respiratory burst. Here, we demonstrate the potential for targeting Kv1.3 channels to control CNS inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
191
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(200 citation statements)
references
References 62 publications
(116 reference statements)
8
191
1
Order By: Relevance
“…PAP‐1 is unlikely to have exerted any direct neuroprotective effects in this assay because experiments performed with PAP‐1 by the NIH Anticonvulsant Screening program did not report any neuroprotection with 10  μ mol/L of PAP‐1 in organotypic hippocampal slices ( n  = 8) exposed to 20  μ mol/L of the excitotoxic agent kainic acid for 4 h and evaluated for propidium iodide uptake in the CA1 and CA3 pyramidal cell layers and the dentate gyrus at 24 h 37. Taken together, these findings and their time course confirm previous observations made with Kv1.3‐blocking peptides and LPS‐stimulated microglia in Transwell cell culture systems11 and suggest that Kv1.3 inhibition increases neuronal survival by reducing microglia‐mediated neuronal killing.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…PAP‐1 is unlikely to have exerted any direct neuroprotective effects in this assay because experiments performed with PAP‐1 by the NIH Anticonvulsant Screening program did not report any neuroprotection with 10  μ mol/L of PAP‐1 in organotypic hippocampal slices ( n  = 8) exposed to 20  μ mol/L of the excitotoxic agent kainic acid for 4 h and evaluated for propidium iodide uptake in the CA1 and CA3 pyramidal cell layers and the dentate gyrus at 24 h 37. Taken together, these findings and their time course confirm previous observations made with Kv1.3‐blocking peptides and LPS‐stimulated microglia in Transwell cell culture systems11 and suggest that Kv1.3 inhibition increases neuronal survival by reducing microglia‐mediated neuronal killing.…”
Section: Resultssupporting
confidence: 88%
“…In addition to T‐cells, Kv1.3 is also expressed in microglia, where in vitro experiments with rodent microglia have shown the channel to be involved in inflammatory cytokine and nitric oxide production and in microglia‐mediated neuronal killing 10, 11, 12, 13, 14. Electrophysiological experiments on slices15 or acutely isolated microglia16 have further demonstrated Kv1.3 currents on activated microglia following MCAO.…”
Section: Introductionmentioning
confidence: 99%
“…Data in Figure 2 show quantitative real-time RT-PCR (qRT-PCR) results comparing expression levels of the Na + /Ca 2+ exchangers, along with a membrane receptor involved in phagocytosis (CR3) and a K + channel (K v 1.3) that is important for the microglial respiratory burst. 24 Routine testing, like that in Figure 2A, showed that the cell cultures used in this study were 99-100% microglia. Based on their morphology 38 the untreated microglia were apparently in an 'alert' state, with most cells having long processes and amoeboid uropods.…”
Section: Resultsmentioning
confidence: 61%
“…Microglia were isolated from brains of 2-3 day-old Wistar rats as we have previously described. [24][25][26] In brief, rat pups were sacrificed by cervical dislocation in accordance with guidelines from the Canadian Institutes of Health Research and the University Health Network. After carefully removing the meninges, whole brain tissue was mashed through a stainless steel sieve (100 mesh; Tissue Grinder Kit #CD-1; Sigma-Aldrich; Oakville, ON, Canada), and then pelleted, resuspended and seeded into flasks with Minimal Essential Medium (MEM) containing 5% fetal bovine serum (FBS), 5% horse serum, and 100 mM gentamycin (all from Invitrogen, Burlington, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…Other penumbra models are based around the popular hypothesis that neuronal damage within the penumbra is propagated by inflammatory responses (microglia activation) initiated from within the ischemic core (Wood, 1995;Schilling et al, 2003). Hence, there are several models which mimic these responses by stimulating microglia, co-cultured with neurons, with exogenously applied chemical activators (Xie et al, 2002;Fordyce et al, 2005). Criti-cisms of these models are, first, that the chemical activators that are used are normally not present during stroke (e.g.…”
Section: Discussionmentioning
confidence: 99%